Din eğitim ve öğretiminde duyguların transferi - Fersahoğlu, Yaşar (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2000)
Transference of Emotions in Religious Education Humans have such dimensions as emotion, thought, and action. Any model of education which can not establish a balance among these dimensions are of no avail. Our emotions express our reactions towards inner and outer phenomena. Among various enıotions love is of a distinctive one. Love is one of the first enıotions to emerge in the child. And Religion teaches that the basic source and object of love is the transcendent God. One who does not achieve such kind of love can not find happiness in life, and is bound to be unproductive. Thus, an intportant question remains here: can transference be used for enıotions as it is used for instruction? The answer to this question is sintply "yes". Transference from concrete to abstract, or from one emotion to anather is possible in orientation of emotions. It is the task of education to expose potential emotions, develop and finally establish a balance among them.